Low-temperature strategy to synthesize highly ordered mesoporous silicas with very large pores - Fan, Jie; Yu, Chengzhong; Lei, Jie; Zhang, Qiang; Li, Tingcheng; Tu, Bo; Zhou, Wuzong; Zhao, Dongyuan (Journal of the American Chemical Society, 2005)
By employing a novel low-temperature synthetic pathway, highly ordered cubic mesoporous materials with hitherto the largest pores (up to 27 nm) and unit cells (up to 44 nm) have been successfully obtained.